KEMUKJIZATAN AL-QUR’AN YANG DAPAT DI BUKTIKAN MELALUI SEEKOR NYAMUK - Adrian Fauzan; Abdul Malik Azila; Ali Akbar (PT. Hasba Edukasi Mandiri, 2025)
The Qur’an is a divine scripture that contains numerous miracles, one of which can be observed through its scientific indications about living beings, including the mosquito as mentioned in Surah Al-Baqarah verse 26. The reference to the mosquito in the Qur’an is not merely a simple example, but a profound lesson about the power of Allah and the perfection of His creation. This study explores how the miraculous nature of the Qur’an can be proven through scientific analysis of the mosquito, focusing on its intricate body structure, survival abilities, and role in human life. By integrating explanations from Qur’anic exegesis (tafsir), Hadith, and modern scientific findings, particularly in the field of biology, this research reveals that the Qur’anic implications correspond precisely with contemporary scientific facts. The mosquito, despite its tiny size, possesses an extraordinarily complex system including a blood-sucking apparatus composed of multiple parts, anesthetic substances that make its bite painless, and a highly accurate mechanism for detecting hosts. These facts confirm that the Qur’an had already pointed to the greatness of Allah’s creation long before modern science discovered it. This study strengthens the understanding that the Qur’an remains relevant and harmonious with the continual progress of scientific knowledge.